2011
DOI: 10.1111/j.1744-1617.2010.01356.x
|View full text |Cite
|
Sign up to set email alerts
|

How Effective Are Court‐affiliated Divorcing Parents Education Programs? A Meta‐analytic Study

Abstract: In this meta-analytic study, we looked at all empirical studies that examined the effectiveness of court-affiliated divorcing parents education programs (DPEs). Overall, we found that DPEs were generally effective. Nineteen studies with a DPE treatment group and no-treatment control group had an overall significant moderate positive effect (d = .39); those who participated in DPEs were about 50% better off in terms of program outcomes compared to those who did not participate. The studies examined five specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
82
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 50 publications
3
82
1
3
Order By: Relevance
“…The empirical literature revealing a correlation between parental alienating behavior and adverse child behaviors would help resolve disputes about the legitimacy of parental alienation as a problem worthy of concern. IMPLICATIONS The relatively high incidence of alienating behavior by divorced parents, both fathers and mothers, reported by our subjects suggests the need for effective parent education programs early in the divorce process (Fackrell, Hawkins, & Kay, 2011;Sigal, Sandler, Wolchik, & Braver, 2011). One goal of such programs would be to reduce the extent to which parents expose their children to potentially alienating behavior.…”
Section: Discussionmentioning
confidence: 94%
“…The empirical literature revealing a correlation between parental alienating behavior and adverse child behaviors would help resolve disputes about the legitimacy of parental alienation as a problem worthy of concern. IMPLICATIONS The relatively high incidence of alienating behavior by divorced parents, both fathers and mothers, reported by our subjects suggests the need for effective parent education programs early in the divorce process (Fackrell, Hawkins, & Kay, 2011;Sigal, Sandler, Wolchik, & Braver, 2011). One goal of such programs would be to reduce the extent to which parents expose their children to potentially alienating behavior.…”
Section: Discussionmentioning
confidence: 94%
“…For example, as Salem et al (2013) described, "It is highly unlikely that such short programs can accomplish the challenging goal of improving children's adjustment and that creating such expectations is problematic" (p. 136). In contrast, Fackrell et al (2011) reported, "It is noteworthy that brief interventions (< 4 hours of instruction), which are more common for mandated programs, seem to produce nearly equivalent benefits to more intense programs . .…”
mentioning
confidence: 77%
“…A recent meta-analysis of divorce education programs affiliated with court systems conducted by Fackrell, Hawkins, and Kay (2011) found that of the 19 studies reviewed that had an intervention group and a control group, divorce education had an overall moderate positive effect size (d = .39). For studies with experimental designs that also examined outcomes for children, divorce education programs had a moderate positive effect size on reported children's outcomes (d = .53).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…First, there is evidence that parent education programs directed at fathers in general have positive effects. Programs for divorcing parents generally have positive effects according to a recent meta-analysis (Fackrell et al, 2011), although some have little or no positive impact on fathers or indeed mothers (Douglas, 2004). Another recent metaanalysis of 16 studies regarding educational programs for resident fathers suggests that they increase father's day-to-day care for children, improve coparenting, improve the quality of the father-child relationship, and lessen child behaviour problems (Holmes et al, 2010).…”
Section: Positive Responses To Separated Fathersmentioning
confidence: 99%